Nutritional Potential of Two Lactogenic Plants after Cooking in the Prevention of Hypogalactia: the Case of Euphorbia hirta L. and Secamone afzelii (Shult) K. Shum. - Prosper, Adepo Yapo; Ibrahim, Fofana; Virginie, Atto (International Journal of Environment, Agriculture and Biotechnology, 2023)
To combat hypogalactia, breastfeeding women in rural areas use certain plants in their cooking to induce lactation. However, the nutritional properties of these local products after cooking are not well known. Thus, the aim of this study is to evaluate the nutritional potential of the leafy stems of two plants such as Euphorbia hirta and Secamone afzelii used in Côte d'Ivoire after cooking. The results obtained indicate the presence of proteins (7.55±0.02% ; 8.486±0.04%), total sugars (16.77±0.13 ; 17.93±0.09), reducing sugars (0.619±0.02% ; 0.872±0.03%) and mineral elements such as calcium (1.12±0.08% ; 1.20±0.10%), iron (0.20±0.03%; 0.32±0.02%) and magnesium (0.15±0.01%; 0.54±0.04%) in aqueous extracts from Euphorbia hirta and Secamone afzelii plants after cooking. These results could justify the culinary use of these food plants, which are potential sources of essential nutrients for improving the quality and quantity of breast milk for young children, through the treatment of breastfeeding disorders in women in general. Both plants deserve be valorized. However, further studies on the toxicity of the Secamone afzelii plant are needed.